2022
DOI: 10.1002/slct.202203048
|View full text |Cite
|
Sign up to set email alerts
|

Acrylonitrile Adducts: An Efficient Adsorbent Media for Removal of Iron from Water

Abstract: Present study establishes a series of acrylonitrile adducts as an effective adsorption media for removal of ferrous ion from water. Adduct synthesis was carried out following aza-Michael addition reaction between primary aliphatic amines and acrylonitrile under mild conditions. The synthesized products were characterised by FT-IR, ESI-MS and 1 H NMR spectroscopy and the particle size was analysed by DLS measurements. Adsorption isotherm study of the adducts showed prominent results. The positively charged iron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
(134 reference statements)
0
2
0
Order By: Relevance
“…These adducts have multiple applications. It has been reported that the adducts showed prominent adsorption of Fe 2+ ion from aqueous media 36 . In addition to it, this work aims to investigate the activity of acrylonitrile adducts against antimicrobial and biological properties.…”
Section: Introductionmentioning
confidence: 95%
“…These adducts have multiple applications. It has been reported that the adducts showed prominent adsorption of Fe 2+ ion from aqueous media 36 . In addition to it, this work aims to investigate the activity of acrylonitrile adducts against antimicrobial and biological properties.…”
Section: Introductionmentioning
confidence: 95%
“…These adducts have multiple applications. It has been reported that the adducts showed prominent adsorption of Fe 2+ ion from aqueous media 24 . In addition to it, this work aims to investigate the activity of acrylonitrile adducts against antimicrobial properties.…”
Section: Introductionmentioning
confidence: 95%